Efektivitas Program Pemberian Makanan Tambahan (PMT) Dalam Perbaikan Status Gizi Kurang pada Balita - Andi Maryam; Andi Elis; Irmayanti (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Undernutrition remains a public health issue requiring urgent attention. This condition has long-term impacts on toddlers' growth, development, and immune function. Therefore, appropriate nutritional interventions are essential to prevent stunting and other health complications in toddlers. This study aimed to evaluate the effectiveness of Supplementary Feeding Program (PMT) in improving the nutritional status of undernourished toddlers in the working area of Waindu Community Health Center, Yapen Islands Regency. This study employed a quasi-experimental design with a pre-test and post-test approach. The sample comprised 30 toddlers aged 12-59 months classified as undernourished. Univariate analysis revealed an increase in the mean weight-for-age Z-score from -2.5 at baseline intervention to -1.7 post-intervention. Furthermore, Pearson correlation analysis demonstrated p<0.001 and r=0.993, indicating a strong positive relationship between pre- and post-intervention Z-scores. In conclusion, the Supplementary Feeding Program (PMT) significantly improved the nutritional status of undernourished toddlers in the working area of the Waindu Community Health Center, Yapen Islands Regency.